Transplant center volume and outcomes in lung transplantation for cystic fibrosis. (17th February 2017) - Hayes, Don; Sweet, Stuart C.; Benden, Christian; Kopp, Benjamin T.; Goldfarb, Samuel B.; Visner, Gary A.; Mallory, George B.; Tobias, Joseph D.; Tumin, Dmitry
Summary: Transplant volume represents lung transplant (LTx) expertise and predicts outcomes, so we sought to determine outcomes related to center volumes in cystic fibrosis (CF). United Network for Organ Sharing data were queried for patients with CF in the United States (US) receiving bilateral LTx from 2005 to 2015. Multivariable Cox regression was used to model survival to 1 year and long‐term (>1 year) survival, conditional on surviving at least 1 year. A total of 2025 patients and 67 centers were included in the analysis. The median annual LTx volumes were three in CF [interquartile range (IQR): 2, 6] and 17 in non‐CF (IQR: 8, 33). Multivariable Cox regression in cases with complete data and surviving at least 1 year ( n = 1510) demonstrated that greater annual CF LTx volume (HR per 10 LTx = 0.66; 95% CI: 0.49, 0.89; P = 0.006) but not greater non‐CF LTx volume (HR = 1.00; 95% CI: 0.96, 1.05; P = 0.844) was associated with improved long‐term survival in LTx recipients with CF. A Wald interaction test confirmed that CF LTx volume was more strongly associated with long‐term outcomes than non‐CF LTx volume ( P = 0.012). In a US cohort, center volume was not associated with 1‐year survival. CF‐specific expertise predicted improved long‐term outcomes of LTx for CF, whereas general LTx expertise was unassociated with CF patients' survival.